Systemic Lithium Chloride Administration Improves Tooth Extraction Wound Healing in Estrogen-Deficient Rats - Duarte,Poliana M. (2020)
Abstract The purpose of this investigation was to evaluate the effects of lithium chloride (LiCl) on the socket healing of estrogen-deficient rats. Seventy-two rats were allocated into one of the following groups: Control, Ovariectomy and LiCl (150 mg/kg/2 every other day orally) + Ovariectomy. Animals received LiCl or water from the 14th day post-ovariectomy, until the completion of the experiment. On the 21st day after ovariectomy, the first molars were extracted. Rats were euthanized on the 10th, 20th and 30th days following extractions. Bone healing (BH), TRAP positive cells and immunohistochemical staining for OPG, RANKL, BSP, OPN and OCN were evaluated. The Ovariectomy group presented decreased BH compared to the LiCl group at 10 days, and the lowest BH at 20 days (p<0.05). At 30 days, the Ovariectomy and LiCl-groups presented lower BH than that of the Control (p<0.05). The number of TRAP-stained cells was the lowest in the LiCl group at 20 days and the highest in the Ovariectomy group at 30 days (p<0.05). At 10 days of healing, the LiCl group demonstrated stronger staining for all bone markers when compared to the other groups, while the Ovariectomy group presented higher RANKL expression than that of the Control (p<0.05). LiCl enhanced bone healing in rats with estrogen deficiency, particularly in the initial healing phases. However, as data on the effects of lithium chloride on bone tissue are still preliminary, more studies related to its toxicity and protocol of administration are necessary before its application in clinical practice.